ISOLATION AND IDENTIFICATION OF ENDOPHYTIC FUNGI FROM TERMINALIA CHEBULA OF EASTERN GHATS, TAMILNADU - S, Rajeswari; R, Revathi; D, Arvind Prasanth (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Endophytic fungi live inside the higher plants, apparently without causing any harm to the hosts and its produce the secondary metabolites are potential antimicrobial activity. Terminalia chebula has been used in Ayurveda, Unani & Homeopathy medicine. In this study an isolate and identify the endophytic fungi from T. Chebula collected from pachamalai hills of the Eastern Ghats, Tamilnadu. Methods: The plant materials were taken and first rinsed in running tap water to remove the dust and the other debris present in it. Segments of approximately 0.5 cm were cut in sterile lancet blades and surface sterilized by agitating in 70% ethanol (5s), followed by treatment with 4% NaOCl (90s) and then rinsed in sterile distilled water (10s).Thirty six (leaf, stem and fruit samples) segments from T.chebula plant are processed for the isolation of endophytic fungi. Results: About 36 segments (12 segments of each part respectively) of the medicinal plant were screened for the isolation of the endophytic fungi. A total of 27 endophytic fungi was isolated and identified from medicinal plant T.chebula. The leaf segments showed a maximum repository for endophytic fungi than the other segments. Among the 27 endophytic fungi, the predominant endophytic fungi isolated belonged to the genera of Alternaria longipes, Curvularia spp, Mucor, phoma spp, Aspergillus niger, Aspergillus flavus and Penicillium spp. In this study majority of the fungi belonged to hyaline hyphomycetes. Conclusion: In this study conclude that the isolation of endophytic fungi from medicinal plant of terminalia chebula. To isolate the 27 endophytic fungi produce the novel bioactive compound. However Further studies are required to screen these endophytic fungi for production of novel Bioactive compounds. Keywords: Endophytic fungi, Terminalia chebula, bioactive compound Â 